PENGARUH CARA BIHUN TERHADAP SIFAT FISIKOKIMIA PADA PEMBUATAN INSTANT STARCH NOODLE DARI PATI AREN - Abdul Rahim (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The research conducted was aimed at increasing the use of arenga starch and finding an optimal processing method of instant starch noodle made of arenga starch. The instant starch noodle was made using a bihon method.  The stages of the bihon  method  process  including  determination  of  starch/water  ratio,  duration  of  cooking,  and  optimal  aging  time.  The starch/water  ratio  and  duration  of  cooking  were  established  based  on  the  degree  of  freedom  of  inter-molecular  binding (gelatinization and retro-gradation) with a minimal score of 80% in accordance with the instant noodle requirement (SNI 01-3551-1994). While, the determination of aging time  was based on physicochemical properties of  the instant starch noodle produced. The analysed physicochemical properties included water content, the degree of freedom of inter-molecular binding, cooking rate, cooking loss, tensile strength, elongation, texture and white degree. The results of the research indicated that the best instant starch noodle process using the bihon method was done at starch/ hot water ratio of 1:0.9 (v/v), cooking duration of 15 minutes, and aging time of 60 minutes. The physicochemical properties of the instant starch noodle were at water content of 8.57%, the degree of freedom of inter molecular binding of 83.23%, cooking rate of 3.31 minutes, cooking loss of 7.06%, tensile strength of 0.09 MPa, elongation of 7.44%, texture of 12.29 N and white degree of 75.10%.